DETERMINING FACTORS OF WORK READINESS OF AGRICULTURAL VOCATIONAL SCHOOL STUDENTS - Agus Yuniawan Isyanto; Ai Tusi Fatimah; Sudrajat Sudrajat; Lidya Nur Amalia (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The competition in the world of work is currently very tight, job seekers are not only competing with other job seekers but also competing with technology that has now replaced the role of humans in the industrial world. Vocational High School is a level of education that is prepared to produce graduates who are ready to work and prepare skilled workers in accordance with their fields of expertise. In line with that, Agricultural Vocational High Schools ideally produce graduates who are skilled and ready to work in the agricultural sector. The study was conducted with the aim of identifying the determinants of the work readiness of Agricultural Vocational High School students to work in the agricultural sector. The study was conducted at Agricultural Vocational High Schools in Ciamis Regency with a sample size of 132 students. The determinants of the work readiness of Agricultural Vocational High School students to work in the agricultural sector were analyzed using multiple linear regression. The results of the study showed that the variables of work motivation, career guidance, work interest, and spiritual intelligence had a significant effect on the work readiness of Agricultural Vocational High School students to work in the agricultural sector, both partially and simultaneously.